Description of the male of Tityus martinpaechi Lourenço, 2001 (Scorpiones, Buthidae) - de Souza, Claudio Augusto R.; Candido, Denise M.; Lourenço, Wilson R. (Zootaxa, 2006)
Tityus martinpaechi Lourenço, 2001 was described based on a single adult female collected in the state of Ceará, Brazil. Subsequently, several scorpions of the genus Tityus were collected in the Chapada de Ibiapaba, Ceará, and sent to the Instituto Butantan in São Paulo, Brazil. One female and one male of these scorpions were identified as belonging to the species T. martinpaechi. Since the male of this species is yet unknown, it is described in this paper.